Estudio de mercado para la sostenibilidad de potenciales emprendimientos de la ciudad de Guaranda, provincia Bolívar, año 2023 - Zaruma Zaruma, Tanya Margarita (2023)
This research work is focused on the Market Study for the sustainability of potential enterprises in the city of Guaranda, Bolívar Province, year 2023, for which it is considered that a market study is a fundamental tool when it comes to knowing about its segments, tastes and preferences, the sustainability of the ventures have decreased due to external factors that cannot be controlled, one of which is the recent outbreak of a pandemic that affected many ventures, reasons for which several owners had to close their businesses and others had to adapt or modify their strategies for this digital era that advanced strongly as the pandemic time passed. The sustainability of the ventures seeks to generate long-term economic benefits. Factors that in one way or another affect businesses causing their closure, for which it is necessary to know them, since their presence has generated fear and the absence of undertaking. Also considering key factors for the sustainability of potential ventures, including financing, the ability to undertake, time or dedication to the business, and age of the entrepreneur.